Zasadnicze myśli encykliki Jana Pawła II Ecclesia de Eucharistia w zastosowaniu katechetycznym - Tkocz, Elżbieta (Studia Pastoralne, 2006)
The article deals with the problem how the main ideas of encyclical Ecclesia de Eucharistia are brought into practice. The subject of cognition are those dogmatic contents included in encyclical which seem to be essential in catechesis focused on formation of young people eucharistic attitudes and awareness. What should be underlined is that eucharistic system employs both, doctrinal contents transmission and supporting young people in choosing life attitudes coming from those contents. Among dogmatic substances of educational implication those are important which deal with sacrificing, communal and eschatological dimension of Eucharist. They may be very helpful in supporting young man trying to understand the essence of real love and looking for value of his human existence. But one can not forget about the central role of testimony in the process of catechesis. Personal testimony of belief and love to Eucharist was given by John Paul II in his encyclical. To become the real witness of prophetic truths, the catechist should follow the example of John Paul II and stay in personal and lively unity with Eucharistic Christ. It is the only condition when he can fulfil the superior aim of his service and get catechumen not only to the meeting with Jesus but also to unifying and deep intimacy with Him.